2021
DOI: 10.1007/s11523-021-00838-x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Treatment Efficacy and Side Effect Profile of Pharmacological Therapies in Asian Patients with Breast Cancer

Abstract: Breast cancer (BC) among Asians accounts for ~ 40% of the global BC burden. Differences in BC risk, presentation, tumor biology, and response to treatment exist between Asian and non-Asian patients; however, Asian patients are often underrepresented in clinical trials. This narrative review summarizes the efficacy and safety of pharmacological therapies for BC in Asian populations, with a focus on outcomes in Asian versus non-Asian patients treated with chemotherapy, hormone therapy, anti-human epidermal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 133 publications
(203 reference statements)
0
5
0
Order By: Relevance
“…While there was a slightly higher incidence of Grade ≥3 AEs in patients receiving olaparib in the subset from Japan than in the global OlympiA population, the number of patients requiring permanent discontinuation of treatment due to AEs was similar between populations. Hematological toxicities occurred at a slightly higher rate in the subset of patients from Japan and are also more common in Asian patients than non-Asian patients following the administration of CT and targeted therapies for breast cancer treatment [ 9 ]. Hematological AEs can generally be managed using an effective dose adjustment strategy [ 9 ], which could further reduce the already low number of patients requiring permanent discontinuation of study treatment due to AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there was a slightly higher incidence of Grade ≥3 AEs in patients receiving olaparib in the subset from Japan than in the global OlympiA population, the number of patients requiring permanent discontinuation of treatment due to AEs was similar between populations. Hematological toxicities occurred at a slightly higher rate in the subset of patients from Japan and are also more common in Asian patients than non-Asian patients following the administration of CT and targeted therapies for breast cancer treatment [ 9 ]. Hematological AEs can generally be managed using an effective dose adjustment strategy [ 9 ], which could further reduce the already low number of patients requiring permanent discontinuation of study treatment due to AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological toxicities occurred at a slightly higher rate in the subset of patients from Japan and are also more common in Asian patients than non-Asian patients following the administration of CT and targeted therapies for breast cancer treatment [ 9 ]. Hematological AEs can generally be managed using an effective dose adjustment strategy [ 9 ], which could further reduce the already low number of patients requiring permanent discontinuation of study treatment due to AEs. AML and MDS were considered AEs of special interest in the OlympiA trial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PRIME II trial on BCS with or without irradiation demonstrated the safety of the omission of PORT in women ≥65 years of age with T1 or T2 tumors (≤3 cm) and node-negative, estrogen receptor (ER)-positive breast cancer [ 6 ]. However, such evidence is limited in non-Asian cohorts, and Asian and non-Asian people differ in the effectiveness and toxicity of systemic therapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several retrospective and prospective trials have been performed in Western countries to omit PORT, the optimal conditions for omitting PORT have not yet been established [9][10][11][12]. In addition, there is limited evidence available in Asian patients, although there are differences in the efficacy and toxicity of systemic therapy [13]. Therefore, we retrospectively reviewed our database.…”
Section: Introductionmentioning
confidence: 99%